Food waste and empty fruit bunches (EFB) characterization for production of biogas by anaerobic co-digestion: article - Mas Rasdan, Muhammad Zulkarnain (2019)
Both of food waste and empty fruit bunches (EFB) are kinds of wasted material that highly potential to be used as a feedstock in composting process of anaerobic digestion. As the composition of these two biomasses consist rich of organic and biodegradable matter, which highly recommended for anaerobic digestion producing biogas production. In anaerobic digestion, feedstock characterization as carbon and nitrogen ratio (C/N ratio), carbohydrate, protein and lipid composition in FW, cellulose, hemicellulose and lignin composition in EFB, play an important role in determining the quantity and yield of biogas production. In this study, C/N ratio was determined by using elemental analyzer meanwhile carbohydrates, protein and lipid composition of food waste and cellulose, hemicellulose and lignin composition of EFB was determined by several analytical methods. By analyze the characteristic of the food waste and EFB, it can theoretically determine and proved in further study, whether the combination of these two biomasses are capable of producing high quantity and yield of biogas which potentially can be used as alternative sources of currently natural gases. Average C/N ratio of food waste obtained was ideal, 11.87 meanwhile C/N ratio of EFB obtained was relatively high, which is not suitable for single digestion and need to be combined with other substrate that have low C/N ratio, where is food waste give it an ideal combination. Carbohydrate, protein and lipid composition of food waste resulting on balance composition especially on Food Waste Type B which is mostly contain of bread. Cellulose, hemicellulose and lignin composition of EFB was also favor for digestion process as it showed low composition of lignin.